Development and Critical Performance Evaluation of an ATmega328–ADXL335 Ground-Vibration Monitoring System for Preliminary Ambient-Noise Measurements - Yolanda Ramadhanty Putri; Menasita Mayantasari; Febrian Dedi Sastrawan; Rahmania Rahmania; Meidi Arisalwadi (Frontier Advances in Applied Science and Engineering, 2026)
Affordable vibration-monitoring platforms can broaden access to seismic instrumentation for education, preliminary field screening, and dense observational networks; however, low cost does not by itself guarantee that a device can resolve weak ambient ground motion or support defensible site-frequency estimates. This study developed and critically evaluated a compact three-component acquisition system integrating an ADXL335 analog accelerometer with the ATmega328P microcontroller of an Arduino Uno R3. The prototype converted analog outputs from the x, y, and z axes into digital acceleration records, displayed the data through the Arduino serial interface, and exported the time series for processing in Geopsy. Bench testing with an oscilloscope produced stable sinusoidal responses of 50.20, 50.10, and 50.30 Hz for the x, y, and z channels, respectively. One-hour measurements were then conducted at five field points. Geopsy returned prominent spectral peaks at 6.8, 3.3, 4.8, 4.2, and 5.02 Hz, while the reported axis-wise consistency indices ranged from 82.32% to 99.98%. The prototype therefore demonstrated functional three-axis acquisition and repeatable electronic response. Nevertheless, the documented one-second logging interval corresponds to a 1 Hz sampling rate and a 0.5 Hz Nyquist frequency; consequently, peaks above 0.5 Hz cannot be interpreted as validated physical site frequencies unless a substantially higher raw sampling rate existed before data decimation. In addition, the absence of reference-seismometer calibration, self-noise characterization, timing verification, and explicit uncertainty analysis prevents the reported percentages from being treated as metrological accuracy. The system is thus best regarded as a proof-of-concept platform for ground-vibration education and hardware development.